The Effectiveness of Thematic Learning Through the Application of the Logan Avenue Problem Solving – Heuristic (LAPS - Heuristic) Model for SDN 331 Borongtellu Students - Ashar Ashar; Syarifah Aeni Rahman; Sitti Salma (Cokroaminoto Journal of Primary Education, 2022)
This research is a type of pre-experimental research with a population of all students at SDN 331 Borongtellu. The sample in this study were fifth grade students at SDN 331 Borongtellu. The instruments used in this research are thematic learning outcomes tests, observation sheets and questionnaires. Data were analyzed using descriptive analysis techniques and inferential analysis. Based on the analysis shows that the students' thematic learning outcomes are completed individually, classically completed and there is an increase in learning outcomes with a gain value of more than 0.29, student activities reach the active criteria, student responses to the Logan Avenue Problem Solving-Heuristic (LAPS-Heuristic) positive with the ability of teachers to manage learning very well. Thus, it can be said that the Logan Avenue Problem Solving-Heuristic (LAPS-Heuristic) learning model is effectively applied in thematic learning to the students of SDN 331 Borongtellu.